Rancang Bangun Sistem Informasi Point Of Sale (Pos) Berbasis Web Pada Usaha Kecil Menengah Menggunakan PHP Dan MYSQL - Sini Siska Kristiani Lase; Mikhael Oktoberyan S.Z. Daeli; Tulus Hati Berkat Zega; Jurisman Waruwu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Sales transaction management in Small and Medium Enterprises (SMEs) is still largely carried out manually using paper records or simple spreadsheet applications. This condition causes various problems such as slow recording processes, high input error rates, difficulty in generating sales reports, and weak inventory management. This project-based research aims to design and implement a web-based Point of Sale (POS) Information System capable of overcoming these problems. The system was developed using native PHP, MySQL, HTML5, CSS3, and JavaScript with the Waterfall development method. The main features include product and category management, an interactive cashier page, four payment methods (cash, QRIS, debit, credit), customer and multi-role user management, and period-based sales reports. System evaluation was conducted using Black Box testing for functionality validation. The Black Box testing results show that all features function according to specification. This system is proven to accelerate the transaction process and automatically generate sales reports, thereby having the potential to improve SME operational efficiency.